2015
DOI: 10.20343/teachlearninqu.3.2.37
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualizing and Communicating SoTL: A Framework for the Field

Abstract: The emerging field of SoTL is an inherently interdisciplinary endeavor, embracing a diverse range of research methods. It desires to be hospitable to a range of disciplinary differences in world views. However, the field lacks coherence in its conceptualization and communication.Ongoing debates in the community concern the use of theory, as well as definitional questions of what constitutes SoTL and the nature of its purpose. This article offers a framework for conceptualizing the field, which attempts to broa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 29 publications
(18 reference statements)
0
28
0
Order By: Relevance
“…SoTL has emerged as a term which slightly competes with educational research, perhaps with a more applied focus. Miller-Young and Yeo (20) stated that SoTL's goals were to deepen an educator's understanding of student learning and explore the effectiveness and desirability of what we do in higher education. SoTL is often targeted by educational researchers as a "weaker" version of what education research is itself (21), however SoTL bears with it an underlying assumption that any expert who teaches a subject must seek out enough pedagogical understanding in order to effectively maintain the production of future experts (22).…”
Section: The Place Of Animal Welfare Scientists In Discipline Based Ementioning
confidence: 99%
“…SoTL has emerged as a term which slightly competes with educational research, perhaps with a more applied focus. Miller-Young and Yeo (20) stated that SoTL's goals were to deepen an educator's understanding of student learning and explore the effectiveness and desirability of what we do in higher education. SoTL is often targeted by educational researchers as a "weaker" version of what education research is itself (21), however SoTL bears with it an underlying assumption that any expert who teaches a subject must seek out enough pedagogical understanding in order to effectively maintain the production of future experts (22).…”
Section: The Place Of Animal Welfare Scientists In Discipline Based Ementioning
confidence: 99%
“…However, in our interviews of seven faculty members from four diverse disciplines as described in Chapter 2 of this issue (Miller-Young and Boman), we observed that many of the bottlenecks described had more to do with ways of being-in-theworld, having affective, relational, and identity elements. As others have argued for SoTL more broadly (Poole 2013;Miller-Young and Yeo 2015), we suggest that taking an interpretive rather than a strictly cognitive approach (as shown through several, if not all of the other chapters in this special issue) would enrich the possibilities inherent in Decoding work. In this analysis, a hermeneutic approach is undertaken as a lens with which to unpack disciplinary elements related to openness to questions, the interpretation of experience, the nature of knowledge, our relationship to language and text, and being-in-the-world.…”
Section: Introductionmentioning
confidence: 63%
“…Although the scholarship of teaching and learning started with a focus on students’ learning and learning processes (Kreber and Cranton ), the field has evolved to include a range of methodologies and epistemologies (Miller‐Young and Yeo ; Poole ) and recognizes the need to address discipline‐centered “ways of thinking, feeling, and behaving” (Coppola and Krajcik , 628) as well as common goals such as critical thinking (Middendorf and Shopkow ). There are several new ways Decoding could be used to address these topics.…”
Section: Implications For Decodingmentioning
confidence: 99%